2004
DOI: 10.1007/s00439-004-1196-5
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary hemorrhagic telangiectasia: ENG and ALK-1 mutations in Dutch patients

Abstract: Hereditary hemorrhagic telangiectasia (HHT) or Rendu-Osler-Weber disease is an autosomal dominant disorder characterized by an aberrant vascular development. The resulting vascular lesions range from smaller mucocutaneous telangiectases to large visceral arteriovenous malformations, especially in the skin, lung, gastrointestinal tract and the brain. Mutations in the genes encoding endoglin (ENG, chromosome 9q34) and activin A receptor type-like kinase 1 (ALK-1, also named ACVRL1, chromosome 12q13) are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
81
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 35 publications
13
81
0
1
Order By: Relevance
“…Our results agree with data reported by other groups on DHPLC analysis performed on many other genes, such as BRCA (Gross et al, 1999), NF1 (De Luca et al, 2004), MLH1 and MSH2 (Holinski-Feder et al, 2001). Furthermore, our prospective DHPLC mutation detection rate (89.3%) is very similar to that obtained by direct sequencing on ENG and ALK1 by other groups (Letteboer et al, 2005;Schulte et al, 2005). Ten different mutations, all consisting in 1-bp substitutions, were undetectable by SSCP analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results agree with data reported by other groups on DHPLC analysis performed on many other genes, such as BRCA (Gross et al, 1999), NF1 (De Luca et al, 2004), MLH1 and MSH2 (Holinski-Feder et al, 2001). Furthermore, our prospective DHPLC mutation detection rate (89.3%) is very similar to that obtained by direct sequencing on ENG and ALK1 by other groups (Letteboer et al, 2005;Schulte et al, 2005). Ten different mutations, all consisting in 1-bp substitutions, were undetectable by SSCP analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Among the Italian patients, we found a high prevalence of ALK1-mutation-carrier probands (41) compared to that for the ENG-mutation-carrier probands (20). Such results, in agreement with the French (Lesca et al, 2004) and Spanish data (Fernandez-Lopez et al, unpublished data reported in the 6 th HHT Scientific Conference, Lyon, 21-23 April 2005), are in contrast with studies on other populations (Letteboer et al, 2005;Abdalla et al, 2005;Kuehl et al, 2005;Schulte et al, 2005). In the French population described by Lesca et al (2004), the higher prevalence of ALK1 mutations was due to both the founder effect and presence of mutational hot-spots which occurred in ALK1 but not in ENG since the authors observed 36 and 34 different mutations in ALK1 and ENG, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Two additional loci, one on chromosome 5 and one on chromosome 7, have been assigned to HHT3 and HHT4, respectively [12,13], although the genes remain to be identified. The overall yield of genetic testing for mutations in ENG, ALK1 and SMAD4 in clinically confirmed cases is high, ranging 78-93% [9,14,15].…”
mentioning
confidence: 99%
“…[21] c.65delA Deletion p.Asp22Alafs*3 [14] c.69delT Deletion p.Val24* [14] c.74_78delAGCCGins176bp Delins p.? [19] c.81dupT Duplication p.Arg28Serfs*10 [22] c.86delG Deletion p.Gly29Alafs*4 [23] c.88C > T Missense p.Pro30Ser [24] c.95T > G Missense p.Val32Gly [25] c.100dupT Duplication p.Cys34Leufs*4 [19] c.100_115del16 Deletion p.Cys34Hisfs*15 [26] c.101G > A Missense p.Cys34Tyr [24] c.102C > A Missense p.Cys34* [25] c.106T > C Missense p.Cys36Arg [14] c.107G > A Missense p.Cys36Tyr [27] c.115_118dupCCAC Duplication p.His40Profs*130 [28] c.121T > C Missense p.Cys41Arg [28] c.128_132delGGCCT Deletion p.Gly43Aspfs*124 [29] c.129delG Deletion p.Pro44Leufs*10 [14] c.136_137delTGinsCT Delins p.Cys46Leu [29] c.138C > A Missense p.Cys46* [19] c.139_140insCG Insertion p.Arg47Profs*8 [30] c.139dupC Duplication p.Arg47Profs*122 [24] Continued c.140G > C Missense p.Arg47Pro [27] c.142G > A Missense p.Gly48Arg [31] c.143G > A Missense p.Gly48Glu [32] c.143_147delGGGCCinsAGCCT Delins p.Gly48_Ala49delinsGluPro [33] c.145dupG Duplication p.Ala49Glyfs*120 [34] c.145delG Deletion p.Ala49Profs*5 [35] c.147delC Deletion p.Trp50Glyfs*4 [36] c.148T > G Missense p.Trp50Gly [37] c.149G > A Missense p.Trp50* [29] c.150G > T Missense p.Trp50Cys [38] c.150G > A Missense p.Trp50* [39] c.152G > A Missense p.Cys51Tyr [34] c.154A > G Missense p.Thr52Ala [24] c.155delC Deletion p.Thr52Lysfs*2 [30] c.164_169delTGGTGC Del...…”
Section: Discussionmentioning
confidence: 99%
“…[30] c.526-1G > A Missense p.? [14] c.526G > T Missense p.Asp176Tyr [37] c.526delG Deletion p.Asp176Thrfs*82 [19] c.536A > C Missense p.Asp179Ala [51] c.540_541insA Insertion p.Asp181Argfs*44 [29] c.563delC Deletion p.Ser188* [19] c.567delG Deletion p.Leu190Serfs*68 [47] c.573delC Deletion p.Phe192Serfs*66 [26] c.590C > T Missense p.Thr197Ile [24] c.593T > A Missense p.Val198Glu [52] c.598C > G Missense p.Arg200Gly [43] c.601C > T Missense p.Gln201* [45] c.601C > A Missense p.Gln201Lys [30] c.602A > G Missense p.Gln201Arg [53] c.602A > C Missense p.Gln201Pro [19] c.611T > G Missense p.Leu204Trp [19] c.614T > G Missense p.Val205Gly [43] c.617A > G Missense p.Glu206Gly [20] c.617_625delAGTGTGTGG Deletion p.Glu206_Val208del [54] c.620delG Deletion p.Cys207Leufs*51 [14] c.623_624dupTG Duplication p.Gly209Trpfs*50 [39] c.626-9_629del13 Deletion p.? [37] c.626-5_634del14 Deletion p.?…”
Section: Discussionmentioning
confidence: 99%